Optimasi Website Duniagoogle.com Untuk Meningkatkan Pengunjung Halaman Menggunakan Metode Search Engine Optimization (SEO) - Efitra Efitra (JURIKOM (Jurnal Riset Komputer), 2022)
The speed of information and competitors in the internet world makes duniagoogle.com website not included in the search list and searches of the first page of Google, thus causing the website to be quiet and not have a maximum end. To overcome the problem of increasing website page visits, it is necessary to optimize using the Search Engine Optimization (SEO) method. The stages in this study were carried out with 2 stages through website analysis and process analysis. While the website SEO method uses 5 techniques, namely creating page segmentation, content structure, speed optimization, keyword research, and utilizing website backlinks. This technique is able to provide more optimal traffic to compete with other website competitors. The goal is that this website can appear on the first page of Google search, so as to get maximum results in the business world using the website. The results of website optimization based on the analysis and application of this method, the main page of the website with the main keyword duniagoogle.com has been indexed in the search engine and google search the first page. A total of 4 posts based on google search short keywords have been found to also appear on the first page of the google search engine. It is certain that the number of statistical website visits has increased from before. In the future, this website will continue to be optimized so that it gets better results. If there is further research related to this website optimization research based on the development of internet technology, it is likely that there are changes and new opportunities, then it must be further researched to be developed, so that the website can survive and compete in the world of Google search engines.